209: ROLE OF ADJUVANT CHEMOTHERAPY IN LOW BURDEN (YPT0-T1N0) GASTRIC ADENOCARCINOMA AFTER NEOADJUVANT CHEMOTHERAPY. (23rd April 2022) - Voron, T; Lambert, C; Piessen, GError! Bookmark not defined; Bonnet, S; Gualtierotti, M; Guiramand, J; Souadka, A; Pezet, D; Gronnier, C
Abstract: Background and aim: Since 2006, perioperative chemotherapy(periCT) has become an established treatment for patients with resectable gastric adenocarcinoma in Europe after the demonstration of a survival benefit in two randomized clinical trials. However, only half of patients included in the periCT arm started adjuvant chemotherapy(adjCT), suggesting a preponderant effect of neoadjuvant chemotherapy(neoCT) on the survival benefit observed. The aim of this study was to assess the benefit of adjCT on disease-free survival in patients with low tumor burden(LTB) (ypT0N0 or ypT1N0) after neoCT. Methods: Data were collected from 30 European centres from 2007 to 2017. Among 2131 included patients, 762 patients received neoCT and 135 had LTB (17.7%), including 40 patients (5.3%) with complete pathological response. Among patients with LTB, 85 (63%) received adjCT(adjCT+) and 50 patients (37%) did not (adjCT-). Propensity score matching analyses were used to compensate for differences in baseline characteristics between ajdCT+ and adjCT- patients. Results: NeoCT regimen was mainly based on platinum-fluoropyrimidine doublet or triplet regimen(88.1%). In univariate analysis, predictive factors for LTB after neoCT were antro-pyloric location, pretherapeutic stage≤cT2, well-differentiated tumor, ≥2 cycles of preoperative chemotherapy, intestinal or mixt-type according to Lauren's classification and non poorly-cohesive cells tumor. Patients in adjCT- group were older and had more frequently severe postoperative complications (≥ grade 3a according to Dindo-Clavien's classification) than patients in adjCT+ group. Despite this, 5-years overall(OS) and disease-free survival(DFS) rates were comparable between adjCT+ and adjcCT- groups, respectively 92% vs. 82% and 89% vs.83%. After propensity score analysis, OS and DFS remain comparable between adjCT+ and adjCT- groups. In adjCT+ group, patients received mostly the same chemotherapy as that received preoperatively (82%). However, severe toxicity was described in 11 patients (13%). Among patients with ypT0N0 response with a follow-up longer than 3 months, 4 patients experienced tumor recurrence or death (11.4%). All of these patients had received adjuvant chemotherapy. Conclusion: Performing adjCT in patients with LTB after neoCT does not seem to provide any benefit on OS or DFS, with non-negligible toxicity rates in counterpart.